High temperature resistant energy-saving coating and its preparation method and application
By using two-component structure and lightweight thermal insulation filler design in kiln coatings, the problem of the short service life of existing high-temperature anti-corrosion topcoat in high-temperature environments is solved, and the effects of efficient thermal insulation and energy-saving and carbon reduction are achieved.
Patent Information
- Application Number
- CN202311098703.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-08-29
AI Technical Summary
The existing high-temperature anti-corrosion topcoat has a short service life under high temperature environments and is prone to problems such as bulging, blistering, peeling and falling off, especially when the kiln is started and stopped, the performance deterioration caused by the alternating temperature of the temperature and heat.
It provides a high-temperature energy-saving coating for kilns, adopting a two-component structure of primer and a topcoat agent. The bottomcoat agent consists of 2.0 modulus sodium silicate, metakaolin, ore powder, etc. The topcoat agent contains lightweight heat-insulating fillers such as expanded vermiculite, expanded perlite, diatomaceous earth zeolite mixed modification materials, and forms a porous structure through geological polymers and gas induction agents to improve thermal insulation performance.
It significantly improves the high temperature resistance and service life of the coating, can maintain heat insulation effect in a high temperature environment above 1000℃, extend the service life of the metal shell on the surface of the kiln, and achieve the purpose of energy saving and carbon reduction.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of high temperature resistant coatings, and in particular to a high temperature resistant energy-saving coating and a preparation method and application thereof. Background Art
[0002] In order to effectively improve the thermal efficiency of the kiln, people have modified the inner wall of the kiln by designing and researching new refractory bricks inside the kiln, redesigning the internal structure of the kiln, and using infrared radiation coatings and heating elements to design and manufacture infrared radiation heating devices. This has been confirmed by production practice and has greatly improved the thermal efficiency and productivity of the kiln, reduced heat loss, and extended the service life of the kiln wall, achieving the goal of energy conservation and emission reduction to a certain extent.
[0003] However, research shows that the heat loss on the surface of the rotary kiln and the preheater at the end of the kiln in the cement plant is quite huge. Huang Yangyang concluded in the thermal calibration and analysis of the 2500 t / d new dry process cement production line that the heat taken away by the exhaust gas at the first outlet of the preheater is 18.99% of the total heat energy, the heat dissipation on the system surface is 10.45%, and the heat taken away by the clinker is 5.14%. The heat dissipation on the system surface alone accounts for 10.45%, which is a considerable heat loss. Therefore, how to reduce the heat loss on the system surface and achieve the purpose of energy saving and consumption reduction is also one of the research hotspots.
[0004] For example, in the Chinese patent application CN109943225A published by Nanjing Dongding New Materials Technology Co., Ltd. on June 28, 2019, a high-temperature resistant anti-corrosion topcoat specially used for furnaces is disclosed, which is composed of the following components in parts by weight: 40-60 parts of epoxy modified silicone resin, 10-25 parts of aluminum powder, 5-10 parts of titanium dioxide, 3-8 parts of coupling agent, 1-3 parts of stabilizer, 0.1-2 parts of wetting dispersant, 0.1-2 parts of leveling agent, and 15-30 parts of solvent; although the above-mentioned high-temperature resistant anti-corrosion topcoat has excellent high-temperature resistance, aging resistance and other properties, and good high-temperature stability, the high-temperature resistant anti-corrosion topcoat uses silicone resin as the main component. Due to the characteristics of silicone resin itself, its service life under high temperature conditions is usually less than half a year, and phenomena such as bulging, blistering, and peeling will occur; and when the temperature alternates between hot and cold due to the start and stop of the furnace, problems such as blistering and peeling are also prone to occur. Summary of the invention
[0005] In view of this, the present invention is indeed necessary to provide a high-temperature resistant energy-saving coating for a kiln and a preparation method and application thereof to solve the above-mentioned problems.
[0006] Specifically, the technical solution provided by the present invention is: a high temperature resistant energy-saving coating, including a primer and a topcoat,
[0007] The primer is a two-component coating composed of component A and component B, and the topcoat is a two-component coating composed of component A and component C.
[0008] Calculated by mass, component A mainly consists of 20-25 parts of 2.0 modulus sodium silicate, 0.5-1.5 parts of sodium dihydrogen phosphate, 0.5-1.5 parts of disodium hydrogen phosphate, 1-2 parts of fumed silica, 2-5 parts of magnesium aluminum silicate, and 1.5-2.5 parts of sodium hydroxide;
[0009] Component B is mainly composed of 15-25 of metakaolin, 10-15 of mineral powder, 5-10 of 200-mesh quartz sand, 15-30 of 80-120-mesh quartz sand, and 10-30 of 40-80-mesh quartz sand;
[0010] Component C is mainly composed of 15-25 of metakaolin, 10-15 of mineral powder, 5-10 of expanded vermiculite, 10-30 of expanded perlite, 10-30 of diatomaceous earth zeolite mixed modified material, 0.5-1 of air entraining agent and 0.5-1 of basalt fiber.
[0011] Wherein, the mass ratio of 2.0 modulus sodium silicate, mineral powder and metakaolin in the top coating agent and the primer is preferably 1: 1-2: 1-2, such as 1: 1: 1, 1: 1.5: 1, 1: 1: 1.5, 1: 1: 2, 1: 1.5: 1.5, 1: 1.5: 2, 1: 2: 1, 1: 2: 1.5, 1: 2: 2. The mass ratio of mineral powder and metakaolin in the top coating agent and the primer is preferably 1: 1-2, such as 1: 1, 1: 1.5, 1: 2, etc. In the primer and the top coating agent, the ratio of the mass of 2.0 modulus sodium silicate to the total mass of metakaolin and mineral powder is preferably 1: 1.5.
[0012] Preferably, the particle size of each raw material in the coating is as follows: the particle size of kaolin is 1000 mesh or more, the particle size of mineral powder is 600 mesh or more, the particle size of expanded vermiculite is 3-5 mm mesh or more, the particle size of expanded perlite is 1-7 mm mesh or more, the particle size of diatomaceous earth zeolite mixed modified material is 400 mesh or more, and the fiber is preferably basalt fiber with a length of 6 mm.
[0013] Sodium silicate is an important component of various coatings. The amount of sodium silicate has a direct impact on the products generated by geopolymerization. Sodium silicate not only provides part of the alkalinity of the reaction, but also mainly provides the silicate ions required for the reaction. The amount of silicate ions determines the form of the main product of the product. Low content results in insufficient product generation and low strength; excessive addition causes silicate ions to be unable to fully participate in the reaction, resulting in the existence of free states. After the reaction is cured, it is easy to form a solidified product on the surface. When the kiln is heated, the crystal water inside the product is not easy to volatilize, causing the coating to burst. Metakaolin provides the silicon-aluminum components required for the product. The main components of metakaolin are silicon and aluminum components. Silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons are formed in the polymerization reaction. This component structure gives the product a certain tensile strength. The main component of mineral powder is calcium. The main product in the geopolymerization process is calcium polymer, which makes the strength of the product play faster. Therefore, the mass ratio of sodium silicate, metakaolin and mineral powder is 1: 1~2: 1~2.
[0014] The topcoat uses geopolymer as an adhesive material and is composed of inorganic materials, and has good high temperature resistance. The topcoat adds expanded vermiculite and closed-cell perlite with low thermal conductivity as lightweight thermal insulation fillers, and diatomaceous earth zeolite mixed modified materials as porous vacuum and semi-vacuum thermal insulation fillers. At the same time, it is combined with an air entraining agent to introduce tiny closed bubbles during the stirring construction. After multiple composite technologies, the topcoat film formed after the topcoat is formed can effectively prevent heat conduction, significantly improve the thermal insulation capacity, achieve excellent thermal insulation performance, and achieve the purpose of energy saving and carbon reduction. In order to make the surface coating film still not easy to fall off when the surface temperature of the metal shell on the surface of the kiln reaches above 1000°C, and has a relatively good thermal insulation effect, the topcoat is a thick coating with a coating thickness of 15 to 20 mm.
[0015] During the construction and application process, the primer uses geopolymer as the main adhesive material, and has a relatively high bonding strength with the metal shell of the kiln, especially with the steel plate shell, and the bonding strength is greater than the cracking strength of the primer film itself formed after the primer is formed, so that the high temperature resistant energy-saving coating is formed at high temperature. The large number of tiny cracks caused by the expansion of the steel plate do not affect the heat insulation effect of the high temperature resistant energy-saving coating. At the same time, the countless microcracks generated by the primer film itself are used to achieve the goal of increasing the expansion coefficient, ensuring that the expansion coefficient of the high temperature resistant energy-saving coating is close to that of the steel plate, so that the primer film is difficult to detach from the steel plate, which can effectively solve the problem that the high temperature energy-saving coating forms hollows during the construction process, resulting in reduced adhesion to the surface of the kiln. The primer is a thin coating, and its coating thickness is preferably 0.1 to 0.2 mm.
[0016] In addition, the quartz sand in the primer is designed to have different particle sizes, which increases the surface roughness of the primer film, greatly enhances the bonding strength between the primer film and the topcoat film, and reduces or avoids the topcoat film from falling off the primer film during use; in this way, when the surface temperature of the kiln shell reaches above 1000°C, the coatings are still not easy to fall off.
[0017] Adding sodium dihydrogen phosphate and disodium hydrogen phosphate to the above-mentioned coating can not only enhance the construction performance of the coating, but also enhance its bonding strength with the metal shell surface of the kiln. The addition of sodium dihydrogen phosphate and disodium hydrogen phosphate is mainly to adjust the setting time of the material. The reaction speed of geopolymer is very fast. If it is not constructed in time, it will lose its construction performance. At the same time, the internal structure of the geopolymer is also constantly changing. At this time, without the adjustment of sodium dihydrogen phosphate and sodium hydrogen phosphate, the construction will often cause the destruction of the internal structure of the material. After the kiln is put into production and the surface temperature of the cylinder rises, the problem of coating shedding is easy to occur; by adding sodium dihydrogen phosphate and disodium hydrogen phosphate, the construction performance can be significantly improved. Magnesium silicate has strong alkali resistance, thickening and anti-sagging properties, which meet the construction requirements of different parts of the product.
[0018] Based on the above coating, the diatomite zeolite mixed modified material is mainly prepared by the following method:
[0019] Mixing and roasting, firstly stirring the diatomite powder and the zeolite powder in a high-speed mixing and modifying machine at high speed until fully mixed to obtain a mixed raw material, then roasting the mixed raw material at a temperature of 400° C. to 450° C. to form a porous material powder, and then performing impurity removal treatment after cooling and drying;
[0020] Secondary modification: adding the impurity-removed porous material powder into the high-speed mixer again, adding stearic acid and stirring at high speed until the temperature of the high-speed mixer rises to 70-80° C., and obtaining the diatomite zeolite mixed modified material after cooling and drying.
[0021] Among them, in the above-mentioned mixed calcination step, the diatomite powder with a particle size of more than 600 meshes and the zeolite powder with a particle size of more than 400 meshes can be subjected to the above-mentioned mixed calcination treatment to minimize the crystallization water inside the material, remove organic matter in the pores and pore diameters, and increase the void volume; at the same time, the zeolite powder and the diatomite powder are fully mixed during high-speed stirring, and powders of different particle sizes are coated with each other, and the powder voids can be formed into a closed hole during high-temperature calcination; the thermal conductivity of the material is reduced, and the thermal insulation formation of the material is improved; the calcined material is dried, cooled, and sieved to remove larger impurities. Therefore, preferably, the mass ratio of the diatomite powder to the zeolite powder is 1:0.9-1.3, such as 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, and the calcination time is 1-3 h, such as 1 h, 1.5 h, 2 h, 2.5 h, 3 h; more preferably, the mass ratio of the diatomite powder to the zeolite powder is 1:1, the calcination temperature is 450°C, and the calcination time is 2 h.
[0022] In the secondary modification step, the diatomite zeolite mixed modified material obtained by the porous material powder after impurity removal treatment and stearic acid modification in a high-speed mixing and modifying machine has a certain surface hydrophobicity, which ensures that when water is added and stirred during construction, the water absorption of the diatomite zeolite mixed modified material is reduced to ensure the vacuum degree of the cavities therein. Preferably, the amount of stearic acid added is 1-2% of the total mass of the diatomite powder and zeolite powder. Since the dissolution temperature of stearic acid is 70-80°C, stearic acid will vaporize at too high a temperature and cannot melt at a low temperature, so the temperature of the secondary modification step is limited to 70-80°C.
[0023] Therefore, the diatomite zeolite mixed modified material is an excellent porous vacuum and semi-vacuum thermal insulation filler, which can ensure that the excellent thermal insulation performance of diatomite and zeolite powder is not reduced during the construction process, and can also effectively reduce the impact of the low strength of diatomite.
[0024] The present invention also provides a method for preparing the above-mentioned high temperature resistant energy-saving coating for kiln, comprising the following steps:
[0025] Preparation of component A: 2.0 modulus sodium silicate, sodium dihydrogen phosphate, disodium hydrogen phosphate, fumed silica, sodium hydroxide and magnesium silicate were uniformly mixed to prepare component A of each coating;
[0026] Preparation of component B: firstly, the metakaolin and the mineral powder are uniformly mixed to obtain a primary mixture; then, the primary mixture, 200 mesh quartz sand, 80-200 mesh quartz sand and 40-80 mesh quartz sand are uniformly mixed to obtain component B for the primer;
[0027] Preparation of component C: firstly, kaolin, mineral powder, diatomite zeolite mixed modified material, air entraining agent and basalt fiber are uniformly mixed to form a secondary mixture; then, the secondary mixture, expanded vermiculite and expanded perlite are uniformly mixed to obtain component C for the topcoat.
[0028] The present invention also provides an application of the above-mentioned high temperature resistant energy-saving coating for a kiln, comprising the steps of:
[0029] Application of primer: firstly completely dissolve component A in water according to the ratio of primer to water of 1:0.3, and let it stand; then add component B and stir evenly to form primer slurry; then apply the primer slurry on the metal shell of the kiln to form a primer film;
[0030] Application of topcoat: first completely dissolve component A in water at a topcoat to water mass ratio of 1:0.7, and let stand; then add component C and stir evenly to form a topcoat slurry; then apply the topcoat slurry on the surface of the base coating film to form a topcoat film.
[0031] Among them, in the application step of the primer, the construction part of the kiln surface can be roller coated or brushed by roller coating or brushing, and the construction thickness should not exceed the particle size of quartz sand of 40 to 80 meshes. After the primer construction is completed and the primer film is formed, the top coating construction can be carried out. Among them, the construction thickness does not exceed the particle size of quartz sand of 40 to 80 meshes, so that the quartz sand of 40 to 80 meshes is dispersed on the coating surface in an incoherent manner, which increases the roughness of the primer film, thereby increasing the interface bonding strength between the primer film and the top coating film.
[0032] In the application step of the topcoat, the construction site of the base coating film can be coated or sprayed by batch coating or spraying, and the construction thickness should not be less than 1.5 cm.
[0033] Therefore, in the above-mentioned high temperature resistant energy-saving coating provided by the present invention, 2.0 modulus sodium silicate, metakaolin and mineral powder are used as raw materials of adhesive materials, wherein 2.0 modulus sodium silicate is used as an activator, metakaolin, mineral powder and other substances are used as silicon-aluminum materials, and a chemical reaction occurs between the activator and the silicon-aluminum material at a certain alkalinity to produce a new substance with a silicon-aluminum long-chain structure, which is used as a film-forming material. The film-forming material has good high temperature resistance and is firmly combined with the kiln metal shell substrate, which can improve or overcome the problem of easy aging in high temperature environment caused by traditional coating adhesives. Expanded vermiculite and closed-cell perlite are used as lightweight thermal insulation fillers, diatomaceous earth zeolite mixed modified materials are used as porous vacuum and semi-vacuum thermal insulation fillers, and air entraining agents can introduce a large number of closed micro-bubbles into the above-mentioned high temperature resistant energy-saving coating during the construction and stirring process. The cooperation of the several is conducive to reducing the thermal conductivity of the coating after film formation, improving the thermal insulation capacity, so that the above-mentioned high temperature resistant energy-saving coating has excellent thermal insulation performance after film formation, and achieves the purpose of energy saving and carbon reduction. Sodium dihydrogen phosphate and disodium hydrogen phosphate can better regulate the geological polymerization reaction rate of kaolin and mineral powder under the action of sodium silicate and sodium hydroxide, avoiding the rapid solidification of the coating slurry due to excessively fast reaction speed in the summer and autumn seasons with higher temperatures, thereby enhancing the construction performance of the coating in higher temperatures such as summer and autumn; in addition, since phosphate reacts with iron at high temperatures, sodium dihydrogen phosphate and disodium hydrogen phosphate introduce phosphate, which can significantly increase the interfacial bonding strength.
[0034] Therefore, the sodium silicate, metakaolin and mineral powder in the above-mentioned high temperature resistant energy-saving coating as film-forming substances have strong bonding with metals, especially steel materials; at the same time, the raw materials in the formulas of the primer and the topcoat cooperate with each other, and the primer and the topcoat cooperate with each other, and the synergistic effect makes the above-mentioned thermal insulation coating brushed on the metal outer surface of high temperature kilns, high temperature equipment, and high temperature pipelines, with the characteristics of convenient construction, high bonding strength, good thermal insulation performance, firm bonding with the metal substrate, and can withstand high temperatures above 1000°C for a long time. In addition, the above-mentioned coating has good freeze-thaw resistance, and it is not easy to have bubbles, peeling and other phenomena when alternating between hot and cold. In addition, alkali, sodium dihydrogen phosphate, disodium hydrogen phosphate and magnesium aluminum silicate are added to the coating, so that the coating still has good construction performance in the summer with higher temperatures, and it can also increase the interface bonding strength between the coating and the metal substrate, and increase the service life of the coating. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0036] The invention provides a high temperature resistant energy-saving coating, comprising a primer and a topcoat, wherein the formula of component A of the primer and the topcoat is the same, and the raw materials are composed of 20-25 of sodium silicate, 0.5-1.5 of sodium dihydrogen phosphate, 0.5-1.5 of disodium hydrogen phosphate, 1-2 of fumed silica, 2-5 of magnesium aluminum silicate, and 1.5-2.5 of sodium hydroxide;
[0037] The raw materials of the primer component B are composed of 15-20 pieces of 1250 mesh metakaolin, 10-15 pieces of 1000 mesh mineral powder, 5-10 pieces of 200 mesh quartz sand, 15-30 pieces of 80-120 mesh quartz sand, and 10-30 pieces of 40-80 mesh quartz sand;
[0038] The raw materials of component C of the top coating agent are composed of 15-20 pieces of kaolin with a particle size of 1250 mesh, 10-15 pieces of mineral powder with a particle size of 1000 mesh, 5-10 pieces of expanded vermiculite with a particle size of 3-5 mm, 10-30 pieces of expanded closed-pore perlite with a particle size of 1-7 mm, 10-30 pieces of diatomaceous earth zeolite mixed modified material with a particle size of more than 400 mesh, 0.5-1 pieces of AE-3 water-soluble air entraining agent, and 0.5-1 pieces of basalt fiber with a length of 6 mm.
[0039] Wherein, the mass ratio of 2.0 modulus sodium silicate, mineral powder and metakaolin in the top coating agent and the primer is preferably 1: 1-2: 1-2, such as 1: 1: 1, 1: 1.5: 1, 1: 1: 1.5, 1: 1: 2, 1: 1.5: 1.5, 1: 1.5: 2, 1: 2: 1, 1: 2: 1.5, 1: 2: 2. The mass ratio of mineral powder and metakaolin in the top coating agent and the primer is preferably 1: 1-2, such as 1: 1, 1: 1.5, 1: 2, etc. In the primer and the top coating agent, the ratio of the mass of 2.0 modulus sodium silicate to the total mass of metakaolin and mineral powder is preferably 1: 1.5.
[0040] The preparation method of the A component is as follows: according to the raw material ratio, sodium silicate with a modulus of 2.0, sodium dihydrogen phosphate, disodium hydrogen phosphate, fumed silica, sodium hydroxide and magnesium silicate are added into a high-speed stirrer and mixed for 2 minutes.
[0041] Preparation method of component B: according to the raw material ratio, first put kaolin and mineral powder into a high-speed stirrer and mix and stir for 2 minutes to obtain a primary mixture; add the primary mixture, 200 mesh quartz sand, 80-200 mesh quartz sand and 40-80 mesh quartz sand into a low-speed stirring pot and mix and stir for 30 minutes to obtain component B for the primer.
[0042] Preparation method of component C: according to the raw material ratio, kaolin, mineral powder, diatomaceous earth zeolite mixed modified material, AE-3 type water-soluble air entraining agent and basalt fiber are added into a high-speed stirrer and mixed for 2 minutes to obtain a secondary mixture. The high-speed stirrer can fully mix the basalt fiber and various materials. The secondary mixture is placed in a low-speed stirring pot with expanded vermiculite and expanded closed-cell perlite and stirred for 30 minutes to obtain component C for the topcoat.
[0043] The stirring speed of the high-speed stirrer used in the present invention is preferably 1500 rpm. The stirring speed of the low-speed stirring pot used in the present invention is preferably 30 rpm.
[0044] The diatomite zeolite mixed modified material used in the following examples is prepared by the following method: diatomite and zeolite powder are mixed and modified, mixed in a ratio of 1:1, and stirred at a high speed of 1500 revolutions per minute for 3 minutes in a high-speed mixing and modifying machine to fully mix the materials; the mixed materials are roasted at a temperature of 450 ° C for 2 h to obtain a roasted mixture; the roasted mixture is added to a high-speed heating mixing and modifying machine again, and 1% stearic acid is added, and the high-speed stirring is performed until the equipment temperature rises to 80 ° C, and the surface modification of the diatomite and zeolite mixture is completed to obtain a diatomite zeolite mixed modified material. Wherein, the diatomite is composed of diatomite with a particle size of 400 mesh, 600 mesh, and 1250 mesh according to a mass ratio of 1: 0.4: 0.1; the zeolite is composed of diatomite with a particle size of 400 mesh, 600 mesh, and 800 mesh according to a mass ratio of 1: 0.4: 0.1.
[0045] The following embodiments of the present invention provide an application of the above-mentioned high temperature resistant energy-saving coating, comprising the following steps:
[0046] Application of primer: firstly completely dissolve the sodium silicate in water at a ratio of 1:0.3 between the primer and water, and let it stand; then add other components and stir evenly to form a primer slurry; then apply the primer slurry on the steel shell surface of the kiln to form a primer film;
[0047] Application of topcoat: first completely dissolve the sodium silicate in water at a topcoat to water mass ratio of 1:0.7, and let it stand; then add other components and stir evenly to form a topcoat slurry; then apply the topcoat slurry on the surface of the base coating to form a topcoat.
[0048] The performance verification tests of the coatings provided in the following embodiments and comparative examples are as follows:
[0049] 1) Test method for earthquake resistance test: drop the sample from a height of 1.5 meters and check the adhesion between the coating and the steel plate after landing, or the area of the drop. The earthquake resistance level judgment criteria are as follows:
[0050] Excellent: The dropped area does not exceed 1 / 5 of the total area, or the dropped part is 1 to 2 cm away from the edge of the sample;
[0051] Good: The dropped area does not exceed 1 / 4 of the total area, or the dropped part is 2 to 3 cm away from the edge of the sample;
[0052] Generally: The drop area does not exceed 1 / 3 of the total area, or the drop area is 3-4cm away from the edge of the sample.
[0053] Poor: Other cases are judged as poor.
[0054] Among them, the anti-seismic performance of the coating provided by the present invention is required to be good or above.
[0055] 2) Bond strength test method: Bond strength test method: The bond strength measurement method in the GB14907-2018 "Steel Structure Fire Retardant Coating" standard is used.
[0056] 3) Thermal insulation performance test method: Thermal insulation performance test method: Use the back-fire baking method to heat the steel plate on the back of the coating using a constant temperature heater. Heat it to 300°C and keep it warm for 2 hours. Then use a thermometer to measure the temperature of the coating surface.
[0057] 4) Freeze-thaw resistance test: Place each sample at room temperature for 48 hours, place it on an electric furnace and bake it at 300°C for 2 hours, cool it to room temperature, put it in a freezer and freeze it for 24 hours, take it out and bake it again for 2 hours after thawing. This is one cycle. If there is no cracking, warping, shedding, peeling, etc. of the surface coating after one cycle, it is considered normal. If there is no abnormality after three cycles, it is a qualified product.
[0058] 5) Constructionability test method: The construction stability at 25°C and 35°C is respectively determined by measuring the initial setting time of the topcoat slurry and the primer slurry after standing to judge the constructionability of the coating; wherein, the initial setting time refers to: the time from the addition of water to the coating to the fluidity of the slurry remaining basically unchanged. Under the same conditions, the higher the construction temperature, the shorter the initial setting time. An initial setting time that is too long or too short is not good. At 25°C, the initial setting time is generally greater than 60 min, preferably 60 to 90 min, and about 60 min is the best. At 35°C, the initial setting time is generally greater than 50 min, preferably 50 to 80 min, and about 50 min is the best.
[0059] Examples 1 to 3
[0060] The formulas of the high temperature resistant energy-saving coatings provided in Examples 1 to 3 are shown in Table 1 below.
[0061] Table 1 Ratio of raw materials by mass for high temperature resistant and energy-saving coatings
[0062]
[0063] Embodiments 1 to 3 of the present invention also each provide an application of a high temperature resistant energy-saving coating, comprising the following steps:
[0064] Application of primer: firstly completely dissolve the sodium silicate in water at a ratio of 1:0.3 between the primer and water, and let it stand; then add other components and stir evenly to form a primer slurry; then apply the primer slurry on the steel shell surface of the kiln to form a primer film;
[0065] Application of topcoat: first completely dissolve the sodium silicate in water at a topcoat to water mass ratio of 1:0.7, and let it stand; then add other components and stir evenly to form a topcoat slurry; then apply the topcoat slurry on the surface of the base coating to form a topcoat.
[0066] Comparative test
[0067] Comparative Example 1 provides a high temperature resistant heat insulating coating, which is mainly different from Example 1 in that the raw materials of component A of the primer and the topcoat are both composed of sodium silicate and do not contain other ingredients. The rest is the same as Example 1.
[0068] Comparative Example 2 provides a high temperature resistant heat insulating coating, which is mainly different from Example 2 in that the raw materials of component A of the primer and the topcoat are both composed of sodium silicate and do not contain other ingredients. The rest is the same as Example 2.
[0069] The results of the seismic resistance, bonding strength, heat resistance, freeze-thaw resistance and construction performance of the high-temperature resistant energy-saving coatings provided by Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 2.
[0070] Table 2 Performance test results of various high temperature resistant energy-saving coatings
[0071]
[0072] It can be seen from Table 2 that compared with the embodiment, the initial setting time of the coating provided in the comparative example is relatively long, which is not conducive to construction; and the seismic performance is relatively poor. When the coating is subjected to external force vibration after film formation, it is easy to fall off in pieces, thereby affecting the thermal insulation effect of the coating.
[0073] The specific application effects of the high temperature resistant energy-saving coatings provided in Examples 1 to 4 are shown in Table 3 below:
[0074] In October 2023, the high temperature resistant heat insulating coating for kiln provided by the above embodiments was applied to the kiln head cover (steel material) of the rotary kiln of Ruyang Zhonglian Cement Plant and has been put into trial use so far, wherein the total thickness of the coating is about 15 mm. The internal temperature of the kiln and the surface temperature of the coating are shown in Table 2 below. The temperature inside the kiln and the surface temperature of the coating were tested using a precision temperature measuring gun.
[0075] Table 3 Application effect table of each embodiment
[0076]
[0077] Analysis test of factors affecting paint workability
[0078] (1) Effect of construction temperature on coating construction performance
[0079] When sodium dihydrogen phosphate and disodium hydrogen phosphate are not added, the comparison of the placement time of the coating slurry at different temperatures is mainly based on the observation of the state of the primer slurry and the topcoat slurry containers formed by stirring when they begin to change significantly. This method mainly relies on the usual construction experience and the degree of understanding of material properties. Since the geological polymerization reaction is a continuous process, there cannot be fixed parameters for investigation when judging the construction time. The primer slurry and the topcoat slurry are judged according to GB / T1346 "Test Methods for Water Consumption, Setting Time and Stability of Cement Standard Consistency". The workability of the coating is judged by the initial setting time.
[0080] Taking the topcoat in Comparative Example 1 as an example, the topcoat slurry was prepared at construction temperatures of 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, and 38°C, and allowed to stand at the corresponding temperatures. The standing time was not less than 60 minutes, and the construction results of each topcoat were shown in Table 4.
[0081] Table 4 Effect of temperature on coating application effect
[0082] Serial number Temperature (℃) Initial setting time / min 1 5 600~700 2 10 420~480 3 15 240~300 4 20 180~240 5 25 80~120 6 30 60~80 7 35 40~60 8 38 25~40
[0083] It can be seen from Table 4 that temperature has a great influence on the coagulation time. As the temperature rises, the reaction speed accelerates sharply.
[0084] (2) Effect of alkali on coating construction performance
[0085] Geopolymerization reacts quickly at high temperatures and is also related to the alkali content. The effect of different alkali contents on the reaction rate was investigated.
[0086] The following study examines the effects of different alkali contents on the placement time in the container and the surface hardening of the coated sample and the thermal insulation effect of the test sample under the conditions of 25°C and 35°C, respectively, taking the topcoat as an example. Among them, compared with the topcoat provided in Example 1, the topcoat of this project does not add sodium dihydrogen phosphate and disodium hydrogen phosphate to the A component of this project, and the other components remain unchanged; that is, the raw materials of the A component include sodium silicate, fumed silica, magnesium aluminum silicate and sodium hydroxide. The construction performance results of each topcoat are shown in Table 5.
[0087] Table 5 Effect of alkali on coating construction performance
[0088]
[0089] It can be seen from Table 5 that the amount of alkali added has a great influence on the reaction speed, but has little influence on the heat insulation effect. However, when the amount of alkali added is low, the phenomenon of falling off after heating occurs. The reason is that the alkali content is insufficient, the alkali excitation reaction is slow or not carried out, and after being coated on the sample, only the water evaporates, causing hardening, so after heating, the phenomenon of falling off occurs. According to this situation, considering the factors affected by the temperature, the alkali content addition is preferably selected to be 1.5 to 2.5 parts by mass, and 1.9 is the best.
[0090] (3) Effects of sodium dihydrogen phosphate and disodium hydrogen phosphate on coating application performance
[0091] When sodium hydroxide is added, the hardening time and product performance are adjusted by adding sodium dihydrogen phosphate and disodium hydrogen phosphate. Sodium dihydrogen phosphate is acidic and disodium hydrogen phosphate is alkaline. The combination of these two products can accurately adjust the alkalinity within a relatively small range. At the same time, the introduction of phosphate can increase the bonding performance between the coating and the base plate.
[0092] The components of the high temperature resistant energy-saving coatings provided in Comparative Example 3, Example 2, and Examples 4 to 7 are basically the same, the main difference being the different amounts of sodium dihydrogen phosphate and disodium hydrogen phosphate added, as shown in Table 6; the other components are the same. The placement time of the above coatings and the seismic performance results of the high temperature resistant energy-saving coatings are shown in Table 6 below.
[0093] Table 6 Effect of the dosage of sodium dihydrogen phosphate and disodium hydrogen phosphate on the coating application performance
[0094]
[0095] It can be seen from Table 6 that the addition of sodium dihydrogen phosphate and disodium hydrogen phosphate can adjust the storage time of the primer slurry and the topcoat slurry in the container, and at the same time has a good effect on improving the seismic performance of the coating. Taking all factors into consideration, the optimal addition amount of sodium dihydrogen phosphate and disodium hydrogen phosphate is 1.5.
[0096] (4) Plasticizer screening test
[0097] In actual construction, there are vertical surfaces and inclined surfaces at the construction site, and the on-site conditions are relatively complex, so there are high requirements for the anti-sagging performance of the coating. Usually, plasticizers are added to make it have better anti-sagging performance. At present, the most commonly used plasticizers in the market are organic or inorganic thickeners. Organic thickeners include starch ethers, cellulose, etc., and inorganic thickeners include attapulgite, bentonite, etc.
[0098] The magnesium aluminum silicate in the top coating agent of Example 2 was replaced by the plasticizers shown in Table 7 respectively, and the other ingredients, process and application remained unchanged. The top coating slurry formed by the corresponding top coating agent was observed. The results are shown in Table 7.
[0099] Table 7 Plasticizer screening test results
[0100] Plasticizers Amylase Cellulose Attapulgite Bentonite Magnesium Aluminum Silicate Phenomenon Floating on the surface Floating on the surface Not thickened Not thickened Obvious effect
[0101] It can be seen from Table 7 that the organic thickener is completely destroyed in the strong alkali system. After being dispersed in water, the organic thickener can usually form a uniform paste. In the strong alkali, it floats on the liquid surface and has no thickening effect. The inorganic thickener has poor performance under strong alkali conditions and fails to achieve the effect of thickening and anti-sagging. Therefore, magnesium aluminum silicate is selected as the plasticizer of the coating provided by the present invention.
[0102] (5) Plasticizer dosage test
[0103] The amounts shown in Table 8 were used to replace the amounts of magnesium aluminum silicate in the topcoat in Example 2, and the other ingredients, processes and applications remained unchanged. The topcoat slurry formed by the corresponding topcoat was applied to the steel plate, and observed to see if there was sagging. The results are shown in Table 8.
[0104] Table 8 Effect of magnesium aluminum silicate dosage on construction performance
[0105] Dosage 1 2 3 4 5 6 Phenomenon No obvious effect No obvious effect Thickening, sagging on vertical surface Thickened, slight sagging on vertical surface Thickening, good anti-sagging effect Thickening, good anti-sagging effect
[0106] It can be seen from Table 8 that: considering comprehensively, the best addition amount of magnesium aluminum silicate is 5 parts by mass, and the effect is obvious. There is no sagging phenomenon when applying 2 cm on the vertical surface, and a good flatness is maintained.
[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A high temperature resistant energy-saving coating, characterized in that: Including primer and topcoat, The primer is a two-component coating composed of component A and component B, and the topcoat is a two-component coating composed of component A and component C. In parts by mass, the component A mainly consists of 20-25 parts of 2.0 modulus sodium silicate, 0.5-1.5 parts of sodium dihydrogen phosphate, 0.5-1.5 parts of disodium hydrogen phosphate, 1-2 parts of fumed silica, 2-5 parts of magnesium aluminum silicate, and 1.5-2.5 parts of sodium hydroxide; The B component is mainly composed of 15-25 of metakaolin, 10-15 of mineral powder, 5-10 of 200-mesh quartz sand, 15-30 of 80-120-mesh quartz sand, and 10-30 of 40-80-mesh quartz sand; The C component is mainly composed of 15-25 of metakaolin, 10-15 of mineral powder, 5-10 of expanded vermiculite, 10-30 of expanded perlite, 10-30 of diatomite zeolite mixed modified material, 0.5-1 of air entraining agent, and 0.5-1 of basalt fiber; Wherein, the diatomite zeolite mixed modified material is mainly prepared by the following method: Mixing and roasting, firstly stir diatomite powder with a particle size of more than 600 mesh and zeolite powder with a particle size of more than 400 mesh in a high-speed mixing and modifying machine at high speed until fully mixed to obtain a mixed raw material, then roast the mixed raw material at a temperature of 400° C. to 450° C. to form a porous material powder, and then perform impurity removal treatment after cooling and drying; Secondary modification: adding the impurity-removed porous material powder into the high-speed mixer again, adding stearic acid and stirring at high speed until the temperature of the high-speed mixer rises to 70-80° C., and obtaining the diatomite zeolite mixed modified material after cooling and drying.
2. The high temperature resistant energy-saving coating according to claim 1, characterized in that: The mass ratio of 2.0 modulus sodium silicate, mineral powder and kaolin in the top coating agent and the primer is 1:1-2:1-2.
3. The high temperature resistant energy-saving coating according to claim 1 or 2, characterized in that: The mass ratio of the mineral powder to the metakaolin in the top coating agent and the bottom coating agent is 1:1-2.
4. The energy-saving coating according to claim 1, characterized in that: The ratio of the mass of 2.0 modulus sodium silicate in the top coating agent and the primer to the total mass of the metakaolin and the mineral powder is 1:1.
5.
5. The high temperature resistant energy-saving coating according to claim 1, 2 or 4, characterized in that: In the mixed calcination step, the mass ratio of the diatomite powder to the zeolite powder is 1:0.9-1.3, and the calcination time is 1-3 h.
6. The high temperature resistant energy-saving coating according to claim 1, characterized in that: In the secondary modification step, the added amount of the stearic acid is 1-2% of the total mass of the diatomite powder and the zeolite powder.
7. A method for preparing the high temperature resistant energy-saving coating according to any one of claims 1 to 6, comprising the following steps: Preparation of component A: 2.0 modulus sodium silicate, sodium dihydrogen phosphate, disodium hydrogen phosphate, fumed silica, sodium hydroxide and magnesium aluminum silicate were uniformly mixed to prepare component A of each coating; Preparation of component B: firstly, the metakaolin and the mineral powder are mixed evenly to obtain a primary mixture; then, the primary mixture, 200 mesh quartz sand, 80-120 mesh quartz sand and 40-80 mesh quartz sand are mixed evenly to obtain component B for the primer; Preparation of component C: firstly, kaolin, mineral powder, diatomite zeolite mixed modified material, air entraining agent and basalt fiber are mixed and stirred with a high-speed stirrer to obtain a secondary mixture; then, the secondary mixture, expanded vermiculite and expanded perlite are added to a low-speed stirring pot for stirring to obtain component C of the top coating agent.
8. An application of the high temperature resistant energy-saving coating according to any one of claims 1 to 6, comprising the steps of: Application of primer: firstly completely dissolve component A in water according to the ratio of primer to water of 1:0.3, and let it stand; then add component B and stir evenly to form primer slurry; then apply the primer slurry on the metal shell of the kiln to form a primer film; Application of topcoat: first completely dissolve component A in water at a topcoat to water mass ratio of 1:0.7, and let stand; then add component C and stir evenly to form a topcoat slurry; then apply the topcoat slurry on the surface of the base coating film to form a topcoat film.
Citation Information
Patent Citations
Special high-temperature-resistance corrosion-resistant finishing coat for kiln and preparation method of finishing coat
CN109943225A
Geopolymer tunnel fireproof coating and preparation method thereof
CN103232197A
Mineral powder base inorganic polymer coating and preparation method
CN106145790A